Yoga intervention and functional pain syndromes: a selective review. (3rd May 2016) - Sutar, Roshan; Yadav, Suresh; Desai, Geetha
Abstract: The definition of functional pain syndromes is varied across literature. No effort has been made to see all functional pain disorder groups under broad nomenclature which would exclude conditions for which pathophysiology is strongly known. Since these disorders are commonly treated with alternative treatment modalities and impose significant burden on health utilization, an effort to look into studies on yoga-based interventions on 'functional pain syndromes' (FPS) was made. This study defined FPS as 'Chronic relapsing remitting pain conditions, the origin of which is difficult to trace with no definite physical pathology on clinical suspicion or available laboratory measures and are valid based on subjective pain reporting, associated distress and socio-occupational dysfunction'. Chronic headache, neck pain, back pain, fibromyalgia, pelvic pain, Irritable Bowel Syndrome, Chronic Fatigue Syndrome, and somatoform pain disorders were included for this review. The review found four meta-analyses on the selected topic both indicating modest efficacy and benefit of yoga in these disorders. Future efforts should be directed to do a large meta-analysis of functional pain syndromes.